Fragmentation patterns of Antarctic icebergs in sea ice: observations and statistical data - Zhenfu Guan; Yan Liu; Xiao Cheng; Teng Li; Mohammed Shokr; Xuying Liu; Shaoyin Wang; Lei Zheng; Zilong Chen (International Journal of Digital Earth, 2025)
Fragmentation is a key process in Antarctic iceberg decay, influencing the Antarctic climate and ecosystems. However, iceberg fragmentation has not been quantified at the pan-Antarctic scale. Using Sentinel-1 data from August to October 2019, we identified 407 fragmentation events in the circum-Antarctic near-coastal zone, with original iceberg sizes ranging from 0.01 km² to 5591.34 km². The Indian Ocean sector had the greatest number of fragmented events, 97% of which involved icebergs less than 1 km², whereas the Bellingshausen–Amundsen Sea sector has experienced the highest number of fragmentation events involving medium to large icebergs. Smaller icebergs (less than 1 km²) were more susceptible to disintegration through highly fractured capsizing, whereas larger icebergs underwent disarticulation. Fragmentation events were less frequent in landfast ice or mélange (∼0.5% monthly), whereas icebergs exceeding 10 km² exhibited a notable increase in the ratio of fragmentation events to the total number of icebergs (more than 15% monthly) when they were in motion and rotating in pack ice. Our findings indicate that during winter and under extensive sea ice cover, internal ocean waves, ocean currents and collisions are key factors influencing iceberg fragmentation.